Filsafat Islam antara Tradisi dan Kontroversi - Syamsuddin Arif (TSAQAFAH, 2014)
Is there such a thing called “Islamic philosophy”? If there is one, what is it? What does it mean for philosophy to be Islamic? How does Islamic philosophy differ from non-Islamic one? Why do some Muslim scholars reject philosophy, ban its instruction, and even scorn its proponents? The present article will address all these questions and seeks to offer a balanced perspective on controversial issues pertaining to philosophy in Islamic intellectual context, drawing upon authoritative, primary sources. The first section deals with definition and terminology, including the disagreement among scholars over which of these is the best appellation: ‘Islamic philosophy’, ’Muslim philosophy’, or ’Arabic philosophy’. This will be followed by a discussion of the main sources of Islamic philosophy and its impacts, as well as the aims and benefits of studying philosophy according to its exponents. The final section provides a critical appraisal of the arguments for and against philosophy that have been put forward by its defenders and its critics. Furthermore, the article also discusses three current approaches to Islamic philosophy, namely the mystical- hermeneutical such as advocated by Leo Strauss and Henry Corbin, the historical- philological study such as practiced Richard Walzer and Dimitri Gutas, and the philosophical-analytical approach such as espoused by Oliver Leaman and Lenn E. Goodman. A final word about the challenges and prospect of Islamic philosophical studies is in order, taking into account recent developments in various parts of the world following revival of interest in Avicenna, Averroes and al-Ghazali.